Reaction Time Based Cognitive Functions and Associated Recovery Heart Rate in Medical Student - Chaudhary, Sailesh; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2022)
Introduction: Physical activity is an indicator of physical function that preserve or promotes cerebral blood flow which in turn is associating with better functioning cognitive function. Cognitive functions can be assessed using reaction time. It is the ability to quick motor response to definite stimulus, while the time that elapses between the sensory stimulation and the motor activity. Aims: To assess the cognitive function of medical students using visual & auditory reaction times in different fitness groups and to correlate values of reaction times to recovery heart rate. Methods: In this cross-sectional study, 57 consenting healthy medical students age 17-30 years, underwent 3-Minutes Step Test to assess their physical fitness along with Auditory reaction time and Visual reaction time to assess their cognitive function. Based on Recovery heart rate which was calculated after 3-Minute step test. Students were categorized into four groups that is good, satisfactory, poor and very poor their Auditory reaction time and Visual reaction time T were measured for these groups. Results: Results showed Auditory reaction time and Visual reaction time was statistically significant when all groups of physically fitness were compared (p-0.014). When pairs of groups were compared significant differences of Auditory reaction time was found good fitness level Vs very poor fitness level in Auditory reaction time (p0.008) and significant difference of Visual reaction time was found between good fitness level Vs satisfactory fitness level in Visual reaction time (p-0.028). Comparison of many other pairs of fitness groups found to be non-significant. Conclusion: Good fitness level has higher cognition which can be achieved by doing physical activity to improve the fitness level.